The influence of pH and organic matter content in paddy soil on heavy metal availability and their uptake by rice plants - Zeng, Fanrong; Ali, Shafaqat; Zhang, Haitao; Ouyang, Younan; Qiu, Boyin; Wu, Feibo; Zhang, Guoping (Environmental pollution (1987), 2011)
The experiments were done to investigate the effect of soil pH and organic matter content on EDTA-extractable heavy metal contents in soils and heavy metal concentrations in rice straw and grains. EDTA-extractable Cr contents in soils and concentrations in rice tissues were negatively correlated with soil pH, but positively correlated with organic matter content. The combination of soil pH and organic matter content would produce the more precise regression models for estimation of EDTA-Cu, Pb and Zn contents in soils, demonstrating the distinct effect of the two factors on the availability of these heavy metals in soils. Soil pH greatly affected heavy metal concentrations in rice plants. Furthermore, inclusion of other soil properties in the stepwise regression analysis improved the regression models for predicting straw Fe and grain Zn concentrations, indicating that other soil properties should be taken into consideration for precise predicting of heavy metal concentrations in rice plants. Soil pH and organic matter content significantly affect heavy metal availability and accumulation in rice plants.